'We're all in the same boat': How participatory songwriting might enhance Singing for Breathing's psychosocial benefits. (1st July 2021) - Yoeli, Heather; Durant, Sharon; McLusky, Sarah; Macnaughton, Jane
Within arts and health, participatory songwriting is recognized as an enjoyable and effective way to encourage emotional connectedness and social cohesion. This study used phenomenological ethnography to consider how collaborative songwriting might enhance the participatory experience of a Singing for Breathing group for people with breathlessness and chronic lung disease. Participants used the songwriting process to celebrate and develop their shared identity, musical and cultural heritage. Songwriting enabled participants to share their lived experiences of the anxiety and social isolation of chronic lung disease, and thereby to explore their being 'all in the same boat' musically, culturally and existentially. When considered within the context of similar singing-based and writing-based research, this study suggests that participatory and collaborative songwriting projects might confer psychosocial benefits to a group and to its members. While further research is needed, we propose that singing groups aiming to improve health should include songwriting.